A Wearable Device-Based System: The Potential Role in Real-time and Remote EEG Monitoring - Arrigo Palumbo; Vera Gramigna; Barbara Calabrese; Nicola Ielpo; Andrea Demeco (Frontiers in Biomedical Technologies, 2024)
Purpose: In recent years, the Electroencephalography (EEG)-based Brain-Computer Interface (BCI) appli-cation has been growing rapidly and has emerged as a technology with high translational potential since it allows disabled people to translate human intentions into control signals and to interact with the external environment without any kinesthetic movement. Individuals with significant health problems can benefit from this technology to improve their independence and facilitate participation in activities, thus improving general well-being and preventing impairments. The rapid advances in technology have led to optimal innovation in the context of wearable health monitoring and remote control solutions. Many wearable devices for capturing EEG signals in daily life have recently been released on the market. Our paper aims to present a wearable de-vice-based system for real-time and remote EEG monitoring, to describe the proposed system modules and the signal processing algorithms, to explore the functionalities of this wearable EEG solution, and to suggest its potential application for daily brain data recordings in the home en-vironment.